O08.4 Rate of sti among selected msm and transgenders in 5 cities of pakistan. (8th July 2017) - Osama, Muhammad
Abstract : Introduction: In Pakistan, males who have sex with males (MSM) and transgender (TG) community is socially excluded from the main stream society which makes them vulnerable towards HIV as well as STI. There are no known surveys previously conducted among MSM in Pakistan. There is a strong need to conduct study on STI rate among MSM/TG in Pakistan. Naz Male Health Alliance (NMHA) is the first ever non-governmental technical support agency in Pakistan that exists to improve the sexual health, welfare and human rights for MSM, TG and their partners. NMHA established 6 CBOs in 5 cities across Pakistan namely Lahore, Rawalpindi, Karachi, Hyderabad and Larkana. The service delivery on the CBO level, includes HIV VCT, BCC, condom/lubricant distribution and STI diagnoses and treatment. The main objective of the study was to see the prevalence of different STIs among MSM and TG population also to recommend the need of interventions at local and policy level. Methods: A total of 2531 comprising DIC (Drop in centre) walk-in clients who had been invited through DIC out-reach program, were provided the treatment of STI services by STI Specialist at CBO (Community Based Organisation) in the 5 cities namely Lahore, Karachi, Rawalpindi, Hyderabad and Larkana. CBOs were technically and financially supported by Naz Male Health Alliance. National guidelines for STI syndromic Management had been followed. Results: 36.07% study population diagnosed by Gonorrhoea, 35.17% diagnosed by Chlamydia, 8.13% diagnosed by Scabies, 4.76% diagnosed by Herpes Simplex, 3.46 diagnosed by Genital Warts, 3.26% diagnosed by Syphilis and 9.15% study population diagnosed by other STIs. Conclusion: There is a need to conduct the surveillance study on STI at National level among MSM population. As these results indicates the prevalence of STI infection among MSM so this highlights the strong need of more STI intervention program with peer lead approach so that MSM can get treatment of STI with no discrimination. Also recognition of MSM population at policy level is highly required.